Fall risk and fitness among older adults enrolled in balance and strength training classes. (7th October 2012) - Goss, C; Thoreson, S; Harrod, C; Clark, L; DiGuiseppi, C
Abstract : Background: The fall risk profile of older adults who participate in community balance/strength classes for fall prevention is not well described. Aims/Objectives/Purpose: We examined fall risk and fitness in older adults taking N'Balance™, an 8-week community-based balance/strength programme. Methods: All 241 first-time participants aged 60+ in 34 consecutive N'Balance programmes held in the study community completed surveys, and staff-administered 30-second chair stand and 8-foot up-and-go tests, during the first and last class. 89% consented to release results to investigators. We calculated fall risk and fitness estimates with Wald 95% CIs. We analysed before-after changes using paired-t or Wilcoxon signed-rank test. Results/Outcomes: Mean participant age was 75.7 years; 82.1% were female, 96.7% had secondary or higher education, and 26.1% (95% CI 20.5% to 32.7%) had BMI≥30. Half (48.1%; 41.3%, 54.9%) had fallen at least once in the past year. Overall, 79.9% (73.9%, 84.8%) had at least one important fall risk (age≥75, fairly-to-very concerned about falling, frequent 'near falls', or fall history). At post-test (83% response), frequency of 'near' falls decreased significantly (Z=−6.816, p<0.001); fear of falling (Short Fall Efficacy Scale-International) declined by 0.8 points (p<0.001), 30-second chair stand improved by 1.7 stands (p<0.001), and 8-foot up-and-go improved by 1.1 s (p<0.001). Significance/Contribution to the Field: Most older adults in community balance/strength classes are at high risk of falls, indicating that such classes are successfully reaching those in need of fall prevention. The N'Balance programme decreased self-reported 'near' falls and fear of falling, and improved fitness; controlled evaluation of its effect on falls is needed.